PELATIHAN KOMPUTER DAN INSTALASI LISTRIK KELOMPOK REMAJA PUTUS SEKOLAH DAERAH RAWAN KONFLIK DI KABUPATEN SIGI - Mukhlis, Baso; Nugraha, Deny Wiria; Kalatiku, Protus P (FORISTEK : Forum Teknik Elektro dan Teknologi Informasi, 2014)
Sigi is one of the youngest district in Central Sulawesi province was divided in 2008. Of the 152 villages, 10 villages are experiencing conflicts between residents. Bora Village and Village Vatunonju which is approximately 20 km from the city of Palu is 2 villages among the 10 villages that are often in conflict. Sources of conflict in general stems from a fight between youth. Increasing the number of teenagers who drop out of school temporarily limited employment is one of the problems that often lead to fights among youth. The low work skills possessed by the youth of this area is an issue that must look for solutions so that they can open up and explore job opportunities. This training aims to provide job skills for young people who are still out of school age. With a working capital given the skills they are expected to open and fill vacancies in areas Sigi continues to build. The training activities carried out for 8 months and was attended by 20 people. After the activity the participants are able to operate Microsoft Word and Excel. Although not all of the material provided can be controlled but this training provides many benefits. Especially for trainee electrical installations are already some people who often help people when there are problems in their electrical istalasi, there's even working at the company electrical installer. Keywords : computer, electricity, conflict